Andrographolide ameliorates aortic valve calcification by regulation of lipid biosynthesis and glycerolipid metabolism targeting MGLL expression in vitro and in vivo. (December 2021) - Wang, Chunli; Huang, Yuming; Liu, Xianqiong; Li, Lanqing; Xu, Haiying; Dong, Nianguo; Xu, Kang
Highlights: Andrographolide (AGP) could inhibit calcific phenotype transforming of valve interstitial cells. Andrographolide (AGP) could attenuate the calcification of aortic valve via regulation of cell metabolism. The calcific aortic valve disease (CAVD) associated metabolites highly enriched in biosynthesis of unsaturated fatty acids and glycerolipid metabolism. AGP visibly ameliorated aortic valve calcification by targeting monoglyceride lipase (MGLL). Abstract: Calcific aortic valve disease (CAVD) is caused by the initiation of the thickening and calcification of valve leaflets by valve interstitial cells (VICs). Cell metabolic changes during the CAVD process are a new field of basic research on this disease. The present study aimed to investigate whether andrographolide (AGP) could attenuate the calcification of aortic valves by regulating cell metabolism. Gas chromatography-mass spectroscopy (GC–MS) metabolome analysis was utilized to investigate the changes in the metabolites of VICs from healthy and CAVD samples. Cell growth and the osteogenic differentiation of human VICs (hVICs) were assessed using a CCK8 assay and Alizarin Red S staining, respectively. The expression of two calcification-related markers, RUNX2 and ALP, was analyzed by quantitative real-time polymerase chain reaction (qRT-PCR) and immunofluorescence staining. Molecular docking was used to detect the interaction between AGP and monoglyceride lipase (MGLL). The high-fat-fed ApoE-/- mice aortic valve calcification animal model was used to verify the effect of AGP on CAVD in vivo. Metabolome analysis showed that the metabolites of VICs from healthy and CAVD samples were highly enriched in the biosynthesis of unsaturated fatty acids and glycerolipid metabolism. The top six highlighted metabolites were selected to reveal a high regulation of lipids in VICs from CAVD. AGP significantly suppressed the calcific differentiation of VICs while it decreased the accumulation of the above six metabolites, 1-monopalmitic, palmitic acid, glycerol, l -asparagine, tetraethylene glycol, and stearic acid induced by osteogenic medium (OM) stimulation. These metabolites were highly correlated with the calcific marker ALP and showed a positive correlation with CAVD. In the comprehensive assessment, MGLL, associated with glycerol synthesis, was selected as the molecular target of AGP in inhibiting the calcific phenotype of transforming hVICs. The in vivo results revealed that AGP visibly ameliorated aortic valve calcification by reducing Von Kossa and ALP staining, which was positively correlated with MGLL expression. AGP ameliorated aortic valve calcification by regulating lipid biosynthesis and glycerolipid metabolism targeting MGLL expression in vitro and in vivo. It is a potent therapeutic supplement that prevents the occurrence of heart valve calcification disease by regulating cell metabolism. Graphical abstract: Image, graphical abstract